Learning by doing? Practical reflections on conducting a systematic review in educational technology research - Bedenlier, Svenja; Bond, Melissa; Buntins, Katja; Zawacki-Richter, Olaf; Kerres, Michael; et al. (Systematic Reviews in Educational Research. Methodology, Perspectives and Application, 2019)
Drawing on an example of a large systematic review that was conducted on the use of educational technology and student engagement in higher education, we provide practical insights into how we proceeded throughout the review phases. Readers and researchers embarking on a systematic review themselves might find the contents of this chapter useful, in order to better prepare themselves for issues that can arise when undertaking such an endeavour.<br
Keywords: Systematic Reviews; Educational Research; Practical Examples for Systematic Reviews; Student Engagement; Educational Technology; Academic Success; Education Research; Open Access